Assessing the Influence of Artificial Intelligence Technologies on the Financial Sustainability of Public Projects in Lagos State, Nigeria (African Journal of Public Administration & Management, 2026)
Sustainable investing has recently attracted considerable attention from policymakers, researchers, and academics. In today's age of AI, societies now rely on an extensive range of data, social media platforms, information management, and data science to ensure their survival and achieve sustainability objectives (Al-Sartawi et al.,2021). Sustainability requires adapting AI technologies (Memdani, 2020; Krüger et al., 2020; Barber et al., 2021; Bauer et al., 2021; Hannoon et al., 2021). AI's true value lies in its capacity to enhance and maintain environmental and social governance (Nishant et al., 2020). According to Craig (2021), the United Nations' estimate of the expenditure required to achieve the Sustainable Development Goals (SDGs) by 2020 was between $5 trillion and $7 trillion. The widespread adoption of intelligent systems has generated additional financial data, creating new challenges that require advanced financial and accounting solutions.
Keywords: Artificial Intelligence; Financial Sustainability; Public Projects